The role of agricultural productivity in economic growth in middle-income countries: An empirical investigation - Arif Eser Güzel; Cemil Serhat Akin (Economic Journal of Emerging Markets, 2021)
Purpose - This study investigates the role of agricultural productivity in economic growth in middle-income countries.